Is There a Role for Biweekly Romiplostim in the Management of Chronic Immune Thrombocytopenia (ITP)? A Report of Three Cases - Jasjit Kaur Rooprai; Karima Khamisa (Case Reports in Hematology)
Romiplostim is a peptibody, which stimulates platelet production by a mechanism similar to that of endogenous thrombopoietin. It has an established indication as second-line therapy in patients with chronic immune thrombocytopenia (ITP). The agent is typically administered weekly; however, there are instances where a biweekly (i.e., alternate week) dosing may be feasible in a select group of patients. We conducted a retrospective case review to evaluate the efficacy and safety of biweekly administration of romiplostim in maintaining a platelet count of >30 × 109/L in three patients with chronic ITP. Treatment was started with a weekly injection (1 µg/kg) with a dose escalation to achieve a platelet count >30 × 109/L. Once stable on weekly romiplostim, these patients received biweekly administration. No bleeding complications were noted during biweekly dosing for these patients. The current findings suggest that lengthening the dose interval of romiplostim is feasible in select patients with chronic ITP to maintain stable platelet counts. Additional studies are therefore warranted to further evaluate biweekly dosing for romiplostim to increase convenience and decrease costs for patients with chronic ITP.